Mass Customization and Sustainability An assessment framework and industrial implementation - Boër, Claudio R.; Pedrazzoli, Paolo; Bettoni, Andrea; Sorlini, Marzio; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
To adapt to global competitive pressures, manufacturers must develop methods and enabling technologies towards a personalized, customer oriented and sustainable manufacturing. Mass Customization and Sustainability defines the two concepts of mass customization and sustainability and introduces a framework to establish a link between the two concepts to answer the questions: Are these two aspects empowering one another? Or are they hindering one another? These questions investigate mass customization as one of the main driving forces to achieve effective sustainability. A methodology to assess the contribution of mass customization to sustainability is developed, providing an assessment model composed by a set of indicators covering the three aspects of sustainability: social, economical and environmental. This is supported and further explained using ideas and new concepts compiled from recent European research. Researchers, scientists, managers and industry professionals alike can follow a set of practical examples and industrial cases, enabling them to easily transfer Mass Customization and Sustainability theoretical concepts into actions to be enforced into their everyday business for gaining competitiveness. Mass Customization and Sustainability also introduces useful concepts for government officials responsible for establishing sustainable policies and regulations, offering methods to compare the results of implementation of such policies.
1.Introduction -- 2.Mass Customization Theory and Implementation Framework -- 3.Sustainability Assessment Model -- 4.Assessment of sustainable MC production in a Selected Test Case -- 5.Ideas and Trends from Research Activities -- 6.Hic Sunt Dracones: Here Be Dragons.
Keywords: Industrial engineering; Production engineering; Engineering economics; Engineering economy; Management; Industrial management; Sustainable development; Industrial and Production Engineering; Engineering Economics, Organization, Logistics, Marketing; Innovation/Technology Management; Sustainable Development